2015
DOI: 10.22256/pubvet.v5n33.1213
|View full text |Cite
|
Sign up to set email alerts
|

Taxa de prenhez em vacas mestiças submetidas ao protocolo de IATF e aplicação de análogo de GnRH 12 dias após a IA

Abstract: This study aimed to evaluate the effect of GnRH administered 12 days after FTAI on pregnancy rate and progesterone levels in crossbred beef cows. Fifty-nine non-pregnant crossbred cows (Bos taurus indicus x Bos taurus taurus) previously selected by gynecologic examination with a body condition score (BCS) of 3.0 (scale of 1 - 5). Cows were randomly assigned to two treatments: TEB (n = 30), on day 0, an intravaginal progesterone releasing device (Primer®) was inserted and cows received i.m. 2.0 mg of estardiol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The reduction in production costs, without interference in production performance, means improvement in the efficiency of the system. Gottschall and Silva (2018) reported a pregnancy rate of 57.6% in beef heifers using third use progesterone devices, a result similar to that found in this study. Gottschall et al (2009) observed pregnancy rates of 61.1% and 49.7% in Aberdeen Angus cows using intravaginal progesterone devices, of 1st and 2nd use , respectively, showing that the reuse of the progesterone device in the protocol TAI is also effective in lactating cows with calf at foot.…”
Section: Variable Odds Ration P Valuesupporting
confidence: 90%
“…The reduction in production costs, without interference in production performance, means improvement in the efficiency of the system. Gottschall and Silva (2018) reported a pregnancy rate of 57.6% in beef heifers using third use progesterone devices, a result similar to that found in this study. Gottschall et al (2009) observed pregnancy rates of 61.1% and 49.7% in Aberdeen Angus cows using intravaginal progesterone devices, of 1st and 2nd use , respectively, showing that the reuse of the progesterone device in the protocol TAI is also effective in lactating cows with calf at foot.…”
Section: Variable Odds Ration P Valuesupporting
confidence: 90%